Angiomotin promotes renal epithelial and carcinoma cell proliferation by retaining the nuclear YAP - Lv, Meng (Oncotarget, 2016)
Renal cell carcinoma (RCC) is one of the common tumors in the urinary system without effective therapies. Angiomotin (Amot) can interact with Yes-associated protein (YAP) to either stimulate or inhibit YAP activity, playing a potential role in cell proliferation. However, the role of Amot in regulating the proliferation of renal epithelial and RCC cells is unknown. Here, we show that Amot is expressed predominantly in the nucleus of RCC cells and tissues, and in the cytoplasm and nucleus of renal epithelial cells and paracancerous tissues. Furthermore, Amot silencing inhibited proliferation of HK-2 and 786-O cells while Amot upregulation promoted proliferation of ACHN cells. Interestingly, the location of Amot and YAP in RCC clinical samples and cells was similar. Amot interacted with YAP in HK-2 and 786-O cells, particularly in the nucleus. Moreover, Amot silencing mitigated the levels of nuclear YAP in HK-2 and 786-O cells and reduced YAP-related CTGF and Cyr61 expression in 786-O cells. Amot upregulation slightly increased the nuclear YAP and YAP-related gene expression in ACHN cells. Finally, enhanced YAP expression restored proliferation of Amot-silencing 786-O cells. Together, these data indicate that Amot is crucial for the maintenance of nuclear YAP to promote renal epithelial and RCC proliferation.